(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study sought to establish how different facets of consumer behaviour have been affected by the Covid-19 pandemic, and how companies in the UK have adopted digital strategies to cope with the challenges that the pandemic has brought about. A desk-based research approach was used. It relied on a wide range of secondary sources such as books, journal articles and publications made by experts in the field of business and consumer behaviour. The main findings from the research highlight a shift of consumer behaviour, increasing the tendency of making online purchases except for essential commodities that have to be physically purchased. This shift has triggered a corresponding increase in adoption of digital technologies for businesses to ensure that they continue making sales amidst lockdowns and movement restrictions. The Covid- 19 pandemic is quite a recent phenomenon and its impacts on consumer behaviour have been explored for just more than a year before this study. Therefore, the long-term impacts may not have been properly documented. Previous studies that were relied upon also had different objectives from this study and as such could impact the accuracy with which this study’s objectives were met. Through analysis of previous studies, this study has provided a new interpretive perspective to existing research on the impact of Covid-19 to consumer behaviour and digital adoption by businesses. It provides valuable insights on how businesses can embrace digital strategies to maintain their relevance to clientele even as their consumer behaviours change.